PENDAYAGUNAAN PERPUSTAKAAN DI BADAN PERPUSTAKAAN, ARSIP DAN DOKUMENTASI PROVINSI SULAWESI UTARA - LESNUSSA, REJUNE JUNITA (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Strategies for achieving maximum service in a library can be done with the use of the library.Library as a source of information is expected not only to serve the public to obtain information, but itcan maintain its existence as an information service institution that develops with the progress ofinformation technology. The purpose of research to gather and analyze the utilization of the library inBadan Perpustakaan, Arsip dan Dokumentasi Provinsi Sulawesi Utara.The methodology used is qualitative, data were collected through observation, interviews andliterature study. The number of informants 14 people. The data obtained were related to the utilizationof the library which were then analyzed through categorization and data reduction.The result of this study shows that in the Library Utilization Badan Perpustakaan, Arsip danDokumentasi Provinsi Sulawesi Utara it is not going well. Existing human resources quality of work isstill very low. The lack of mastery of information technology and the slow pace in providing serviceslibrarian. State library collection is irrelevant, Means still manual information retrieval, yet has thefacilities, such as internet and OPAC, covered services system has not gone well.Conclusion is that the utilization of the library in Badan Perpustakaan, Arsip danDokumentasi Provinsi Sulawesi Utara have not been going well, human resources are still lackingquality work, which is not relevant collections, facilities and infrastructure are still lacking and closedthe service system has not gone well. So that should make improvements human resources througheducation and training levels. Increasing the number of employees in particular librarian libraryeducational background. Procure to increase the number of library collections. Adding a means oftracking information such as OPAC and the Internet. Fixing system covered services for smoothservice information.Key words : Library Reforms, Human Resources, Collection, Fasilities and Infrastrukture, SystemService